Peningkatan Daya Dukung Tanah Litosol melalui Distribusi Mikroba dengan Teknologi Smart Bioosildam - Nugroho Widiasmadi (Journal on Education, 2023)
This study aims to control the health and fertility of the soil naturally. This research was conducted on litosol land used for plantations by observing the distribution pattern of the electrolyte conductivity level at each soil depth through microbial activity. This study observed over a period of time through a microcontroller sensor the changes in soil parameters such as: soil acidity level, infiltration rate, electrolyte conductivity level and porosity level observed from the soil infiltration rate. Using the simulation method with two (2) types of bioholes, it can be seen the increase in EC at each depth at a certain time period. This method uses Smart Biosoildam (Biodam) technology which can be simulated to match the actual process (real time). From graphic observations and EC standards, it can be seen that the ability of the soil to provide nutrients in the root growth zone can be used as information to determine the schedule and distribution pattern of planting both during the vegetative growth period and the generative growth period. So that it can be known the effective planting distance and biohole distance in order to be able to provide nutrients during the vegetative and generative periods. The distribution of nutrients can be monitored through sensors that convert analog parameters on the microprocessor into digital information that is sent via wifi in real time. Simulation of sandy beach soil fertility based on the number of microbial population = 108/cfu. Variable 1: Soil fertility value of electrolyte conductivity/EC value at a depth of 26 cm from 580 uS/cm to 1238 uS/cm on day 35 and from 1238 uS/cm down to 1090 uS/cm on day 40. Variable 2: Soil fertility values from electrolyte conductivity / EC values at a depth of 24 cm from 550 uS / cm to 968 uS / cm on day 35 & from 968 uS / cm down to 842 uS/cm on day 40.